Correction: Metformin exhibits preventive and therapeutic efficacy against experimental cystic echinococcosis - Loos, Julia Alexandra (2017)
Metformin (Met) is an anti-hyperglycemic and potential anti-cancer agent which may exert its anti-proliferative effects via the induction of energetic stress. In this study we investigated the in vitro and in vivo efficacy of Met against the larval stage of Echinococcus granulosus. Metformin showed significant dose- and time-dependent killing effects on in vitro cultured protoscoleces and metacestodes. Notably, the combination of Met together with the minimum effective concentration of ABZSO had a synergistic effect after days 3 and 12 on metacestodes and protoscoleces, respectively. Oral administration of Met (50 mg/kg/day) in E. granulosus-infected mice was highly effective in reducing the weight and number of parasite cysts, yet its combination with the lowest recommended dose of ABZ (5 mg/kg/day) was even more effective. Coincidentally, intracystic Met accumulation was higher in animals treated with both drugs compared to those administered Met alone. Furthermore, the safe plant-derived drug Met exhibited remarkable chemopreventive properties against secondary hydatidosis in mice. In conclusion, based on our experimental data, Met emerges as a promising anti-echinococcal drug as it has proven to efficiently inhibit the development and growth of the E. granulosus larval stage and its combination with ABZ may improve the current anti-parasitic therapy.